Kedah go down fighting to T-Team in first leg thriller - Noh, Dasheer (The Star (Metro North), 2014)
TERENGGANU'S T-Team toiled to a narrow one-nil victory over Kedah in the President Cup quarter-final first leg soccer encounter at the Universiti Utara Malaysia (UUM) mini stadium in Sintok.